Investigating the coumarin capability in chalcogenide 20TI2Se-80Pr2Se3 system based photovoltaics - Soylu, M.; Dere, A.; Ahmedova, C.; Barim, G.; Al-Sehemi, Abdullah G.; Al-Ghamdi, Ahmed A.; Yakuphanoğlu, Fahrettin (Pergamon-Elsevier Science Ltd, 2018)
Chalcogenide films containing various contents of coumarin (CO) are deposited on the p-type Si substrates. Al/coumarin doped chalcogenide films/p-Si contact exhibits a rectifying behavior. The electrical and photoresponse properties of the prepared diodes are characterized by current and capacitance measurements under various illumination intensities. The addition of coumarin to TI2Se-Pr2Se3 significantly affects the characteristic parameters of diodes. Kohlrausch function is used as an appropriate way to obtain the photo charge density (Pp) and the relaxation time constant from the photocurrent/capacitance transients. It is shown that coumarin doped chalcogenide films have a potential to obtain the photocarrier generation. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Chalcogenide films; Coumarin; Heterojunction; Light-sensing